Galectin‐1 interacts with the human endogenous retroviral envelope protein syncytin‐2 and potentiates trophoblast fusion in humans. Issue 11 (7th September 2019) - Toudic, Caroline; Vargas, Amandine; Xiao, Yong; St‐Pierre, Guillaume; Bannert, Norbert; Lafond, Julie; Rassart, Eric; Sato, Sachiko; Barbeau, Benoit
Abstract : Syncytin (Syn)‐2 is an important fusogenic protein that contributes to the formation of the placental syncytiotrophoblast. Galectin (Gal)‐1, a soluble lectin, is also involved in trophoblast cell fusion and modulates the interaction of certain retroviral envelopes with their cellular receptor. This study aimed to investigate the association between Syn‐2 and Gal‐1 during human trophoblast cell fusion. This association was evaluated in vitro on primary villous cytotrophoblasts (vCTBs) and cell lines using recombinant Gal‐1 and Syn‐2‐pseudotyped viruses. Using lactose, a Gal antagonist, and Gal‐1‐specific small interfering RNA (siRNA) transfections, we confirmed the implication of Gal‐1 in vCTBs and BeWo cell fusion, although RT‐PCR and ELISA analyses suggested that Gal‐1 alone did not induce syncytialization. Infection assays showed a specific and significant effect of Gal‐1 on the infectivity of Syn‐2‐pseudotyped viruses that depended on the expression of major facilitator superfamily domain‐containing 2A (MFSD2a). Moreover, Gal‐3, another placental Gal, did not modulate the infectivity of Syn‐2‐positive viruses, strengthening the specific association between Gal‐1 and Syn‐2. Interestingly, Gal‐1 significantly reduced the infectivity of Syn‐1‐pseudotyped viruses, suggesting the opposite effects of Gal‐1 on Syn‐1 and ‐2. Finally, coimmunoprecipitation experiments showed a glycan‐dependent interaction between Syn‐2‐bearing virions and Gal‐1. We conclude that Gal‐1 specifically interacts with Syn‐2 and possibly regulates Syn‐2/MFSD2a interaction during syncytialization of trophoblastic cells.—Toudic, C., Vargas, A., Xiao, Y., St‐Pierre, G., Bannert, N., Lafond, J., Rassart, E., Sato, S., Barbeau, B. Galectin‐1 interacts with the human endogenous retroviral envelope protein syncytin‐2 and potentiates trophoblast fusion in humans. FASEB J. 33, 12873–12887 (2019). www.fasebj.org